2002
DOI: 10.1046/j.1464-4096.2001.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral compared with unilateral percutaneous nephrolithotomy

Abstract: Objective To compare simultaneous bilateral percutaneous nephrolithotomy (SBPCNL) and unilateral PCNL in separate sessions in patients with bilateral renal stones for several variables before and after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
1
23
1
Order By: Relevance
“…[18][19][20][21][22][23] Percutaneous stone surgery also has been employed with success in children, the elderly, and the morbidly obese and in a bilateral synchronous fashion. [24][25][26][27][28][29] The results of this survey clearly show that PCNL has become a routine part of urologic training, which has led to a large number of younger urologists performing this procedure. Of the survey participants 30 to 40 years of age, 93.6% answered they were trained to perform PCNL during residency, and 90.1% answered that they were comfortable performing PCNL.…”
Section: Discussionmentioning
confidence: 85%
“…[18][19][20][21][22][23] Percutaneous stone surgery also has been employed with success in children, the elderly, and the morbidly obese and in a bilateral synchronous fashion. [24][25][26][27][28][29] The results of this survey clearly show that PCNL has become a routine part of urologic training, which has led to a large number of younger urologists performing this procedure. Of the survey participants 30 to 40 years of age, 93.6% answered they were trained to perform PCNL during residency, and 90.1% answered that they were comfortable performing PCNL.…”
Section: Discussionmentioning
confidence: 85%
“…Several combinations have been reported, such as open radical surgery with an endoscopic procedure, laparoscopic surgery with an endoscopic procedure, two endoscopic procedures, two open surgical procedures, two laparoscopic procedures, etc. [10][11][12][13][14][15] The primary concerns for a combined procedure are those related to patient safety, length of the procedures, technical difficulties in performing the procedures simultaneously, and impact of one procedure on the outcome of the other if performed simultaneously. This is especially important when one of the surgeries involves a major resection or reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of bilateral simultaneous percutaneous nephrostomy has been demonstrated in the literature [7,8] . Holman et al [9] compared the complications of this procedure with unilateral percutaneous nephrostomy performed in two sessions and found that stone-free rates, renal impairment and the complication rates were similar. To our knowledge, literature on bilateral percutaneous nephrostomy in a patient with hemophilia is non-existent.…”
Section: Discussionmentioning
confidence: 99%